The Role of Madurese Ulama in Maintaining Halal Practices in Society: A Phenomenological Study in Dasuk District, Sumenep - Sajidah; Sarkawi, Sarkawi; Lailatul Qadariyah (Penerbit Hellow Pustaka, 2025)
This research aims to reveal the role of Madurese ulama in maintaining halal practices in the community of Dasuk District, Sumenep Regency. Through a qualitative approach with phenomenological methods, this research explores the subjective experiences of the community and ulama in understanding and internalizing halal values ​​in everyday life. Data was obtained through in-depth interviews, observation and documentation of the religious and socio-economic activities of the Dasuk community. The research results show that ulama play a role as educators, moral supervisors, and social role models who guide society to consistently implement halal principles, not only in consumption but also in work and social interactions. Ulama use a gentle and contextual da'wah approach, such as recitations and informal discussions, to instill awareness about the importance of halal. The main challenges faced include differences in people's levels of understanding, the influence of modernization, and changes in lifestyle. In conclusion, the role of village ulama in Dasuk is very significant as moral and cultural agents in maintaining the continuity of halal values ​​amidst the social dynamics of Madurese society.